Geoprometna valorizacija prostora nacionalnog parka ’Paklenica’ - Malić, Adolf (Promet - Traffic&Transportation, 2012)
Paklenica National Park, covering an area of 3.617 ha,( 1.447 acres) belongs to the group of smaller Croatian nationalparks. It is situated on the Southern slopes of Mount Velebit descendingto the lower coast region, near the Adriatic Highwayand the small town of Starigrad-Paklenica. From the NationalPark, it takes approximately 45 km (26 miles) by road to thenearest/own of any size, Zadar. The sea routes from StarigradPaklenicato Rijeka and Zadar; passing through the LowerVelebit Channel (Podvelebitski kanal) and the Pag and the VirPassages (Paski i Virski prolaz), are not used for public transportas regular ferry and ship links. From the East, Paklenica isclosed by the high Velebit ridge running from Rujan to SveloBrdo. Traffic access to the National Park is therefore easiestfrom the low coastal area from the Southern Starigrad-Paklenicasuburb.The main access route to Paklenica National Park today isthe Adriatic Highway, or E-65 road.